Analisis Pola Nilai Akademik Siswa Ma Dengan Non-Boarding Di Pondok Pesantren Tradisional Dengan Menggunakan Formal Concept Analysis - Supu, Nisfa Daud; Hidayat, Taufiq; Rahmadi, Ridho (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The success or failure of learning objectives in the learning process is greatly influenced by how the learning process is experienced by students. One of the successes of students in education is shown by their academic achievement. The results of the evaluation of a learning process are usually expressed in quantitative form (numbers) which are often applied in evaluating learning scores or grades. This study focuses on analyzing the academic scores of general and religious subjects of students in Class IX Non-Boarding Madrasah Aliyah. The concept of analysis Formal Concept Analysis (FCA) is used as a data analysis method because it is able to represent data and model it into objects and attributes. In this study the FCA method was used to be able to analyze the academic excellence of students at boarding madrasah schools in general subjects or religious subjects. The research objective was to determine the pattern of success in student academic scores and to determine the model of student achievement academically specifically for general subjects. The results of the analysis carried out on the academic scores of 200 students of the Class IX Non-Boarding Madrasah Aliyah in general and religious subjects, it can be concluded that the average student has good and good enough scores, there are general subjects who also have good and quite good scores in the subject. religious lessons.